Effects of solar radiation modification on precipitation extremes in Southeast Asia: Insights from the GeoMIP G6 experiments - Ze-Qian Feng; Mou Leong Tan; Liew Juneng; Mari R. Tye; Li-Li Xia; Fei Zhang (Advances in Climate Change Research)
Solar Radiation Modification (SRM) has been proposed to reduce global temperatures by reflecting more solar radiation into space, but its effects on precipitation extremes across Southeast Asia remain uncertain. This study evaluates the impacts of two SRM strategies on precipitation extremes in Southeast Asia, using the multi-model ensemble mean from five climate models in the Geoengineering Model Intercomparison Project Phase 6 (GeoMIP6). Under a high-emission scenario (SSP585), two SRM approaches are tested: injecting sulfur dioxide (G6sulfur) into the stratosphere and reducing the solar constant (G6solar) to maintain radiative forcing at the level of a moderate-emission scenario (SSP245). Bilinear interpolation and linear scaling were used to downscale and bias-correct daily precipitation data before calculating precipitation extreme indices, respectively. The results show that G6sulfur causes more regional variation in annual total and mean wet day precipitation, the average daily precipitation on days with ≥1 mm rainfall, compared to G6solar. In areas like central Borneo, northern mainland Southeast Asia, and eastern Indonesia, the annual maximum 1-d precipitation per year is projected to increase by 30%–50% under SSP585 relative to the historical 1995–2014 baseline period but this rise could be reduced to around 20% by SSP245, G6sulfur, or G6solar. G6sulfur has less influence on continuous wet and dry spells than G6solar, yielding results closer to SSP585. Both SRM strategies lower the projected increase in heavy precipitation days, except in areas like East Coast Peninsular Malaysia, Nusantara Indonesia, and East Timor. In conclusion, SRM may effectively mitigate increases in extreme precipitation events in most of Southeast Asia, but G6solar provides a more consistent reduction, while G6sulfur shows more complex spatial responses.